S115 How do the UK countries compare for chronic obstructive pulmonary disease primary care?. (12th November 2019) - Stone, PW; Feary, JR; Roberts, CM; Quint, JK
Abstract : Background: The four UK devolved governments are responsible for healthcare in their respective countries, meaning that healthcare commissioning and incentivisation can differ between them. Wales is the only country to receive national audits of COPD primary care. Although desired, a COPD primary care audit has not been possible in other UK countries because of patient confidentiality concerns. This study aimed to use a large UK primary care database to investigate how the three UK countries without audits compare to Wales for COPD primary care. Methods: The 2017 Welsh COPD Primary Care Audit was replicated in the Clinical Practice Research Datalink (CPRD), generating a COPD cohort for the period 01/04/2015 to 31/03/2017. Logistic regression was used to explore association between country and seven outcomes (table 1 ). Logistic regression models were adjusted for age, sex, and comorbidities (diabetes, hypertension, coronary heart disease, stroke, heart failure, painful condition [repeat analgesic prescriptions], lung cancer, asthma, bronchiectasis, depression, anxiety, severe mental illness [psychotic disorders], and osteoporosis). Results: Results of audit analyses in Welsh CPRD practices were comparable to the 2017 Primary Care Audit. Results of logistic regression are presented as odds ratios relative to Wales (table 1 ). English, Scottish, and Northern Irish (NI) COPD patients were significantly less likely to have confirmation of airway obstruction and a pulmonary rehabilitation (PR) referral, but were significantly more likely to have the influenza immunisation. Scottish patients were significantly less likely to have chest X-ray confirmation of diagnosis, an MRC grade, or record of smoking status. English and NI patients were significantly more likely to have a record of MRC grade and smoking status. English and Scottish patients were significantly less likely to receive smoking cessation treatment, whereas NI patients were significantly more likely to receive it. Conclusion: There is a shortfall in all UK countries in delivering aspects of COPD care, and this seems to be particularly pronounced in Scotland. More favourable results from Wales may reflect better adherence to national guidelines or better recording of data in response to participation in national audits. Low levels of PR referral from UK countries other than Wales should be investigated and addressed.